Effect of microwave electromagnetic radiation on the structure, photoluminescence and electronic properties of nanocrystalline silicon films on silicon substrate - Kaganovich, E.B.; Kizyak, I.M.; Kirillova, S.I.; Konakova, R.V.; Lytvyn, O.S.; Lytvyn, P.M.; Manoilov, E.G.; Primachenko, V.E.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We studied the effect of microwave electromagnetic radiation on silicon low-dimensional structures. The nanocrystalline silicon (nc-Si) films on p-Si substrate were formed with pulsed laser ablation. The surface morphology of films was studied with atomic force microscopy. We made X-ray phase analysis of films and measured strains in the structures obtained using X-ray diffractometry. We also investigated the time-resolved photoluminescence (PL) spectra and temperature dependence of photovoltage for the nc-Si/p-Si and nc- Si<Au>/p-Si structures, both before and after exposure to magnetron microwave radiation of moderate (1.5 W/cm²) irradiance. It was shown that after microwave irradiation photovoltage in the nc-Si films, as well as electron trap concentration in both the films and p-Si substrates, decrease. After irradiation of the nc-Si/p-Si structures the density of interfacial electron states (IES) decreases, while both PL intensity and relaxation time increase. At the same time irradiation of the nc-Si<Au>/p-Si structures that had high values of PL intensities and relaxation times before irradiation results in decrease of these values, as well as somewhat increases the density of IES. Higher (7.5 W/cm2) irradiance of microwave field impairs the PL properties (to the point of complete disappearance of PL). In addition it induces changes in film structure resulting, in the course of time, in decrease of strains in the structures studied. We discuss some mechanisms for microwave field effect on the properties of these structures.